Analis Sistem Pembelajaran Bahasa Arab di Ma’had Tahfidz Kitabina Tanjung Morawa - Abdul Sopian Efendi Nasution; Ibrahim Hasan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is motivated by the Arabic language learning system implemented at Ma'had Tahfidz Kitabina Tanjung Morawa, which makes the majority of students experience difficulties in speaking Arabic. To achieve the goals of learning Arabic carried out by an educational institution, including Ma'had Tahfidz Kitabina, a good Arabic language learning system is definitely needed. Learning Arabic ideally allows students to master the four language skills (al-istima', al-kalam, al-qira'ah and al-kitabah) functionally and proportionally. The method used in this research is a qualitative research method. This research uses two types of data sources, namely primary data and secondary data. In collecting primary data, researchers take data directly from informants through interview, observation and documentation techniques. The data analysis techniques used by researchers are Data Reduction, Data Display, and Conclusion/Verification. The results of this research are that there are two Arabic language learning systems used at Ma'had Tahfiz Kitabina Tanjung Morawa, namely: 1) Assessment system. The study system is teaching Arabic with a religious motif that emphasizes the memorization method in the form of providing Arabic vocabulary (mufrodat) in the morning from the ustadz in the dormitory. 2) Management system. The management system in the dormitory uses a system called the sub-district system with the presence of a dormitory head, language, cleanliness, health, guests, and so on. By implementing the Arabic language learning system at Mahad Tahfidz Kitabina, students can increase their memory of the material provided by the teacher and increase students' interest in learning Arabic so that students are motivated by this learning system.